2017
DOI: 10.2118/178886-pa
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance of Annular-Pressure-Buildup Mitigation Techniques

Abstract: Summary Subsea wells use annular-pressure-buildup (APB) mitigation devices to ensure well integrity. We define mitigation techniques that control APB by reducing lateral heat loss from the production tubing to the wellbore as Type I techniques. Mitigation techniques that control the stiffness (psi/°F) of an annulus by modifying its contents and boundaries are defined as Type II techniques. Although the physics of APB mitigation is well-understood, the reliability of a mitigation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…They proposed several active and passive methods of APB mitigation. Udaya et al (2017), in their studies, concluded that it is extremely difficult to quantify the reliability of a mitigation strategy or its corresponding interaction with other parts of the wellbore. Udaya et al used a quantitative approach to design APB mitigation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed several active and passive methods of APB mitigation. Udaya et al (2017), in their studies, concluded that it is extremely difficult to quantify the reliability of a mitigation strategy or its corresponding interaction with other parts of the wellbore. Udaya et al used a quantitative approach to design APB mitigation strategies.…”
Section: Introductionmentioning
confidence: 99%